Development of a Mobile-Based Interactive Digital System for Managing and Evaluating Participation in Open House Events - ภุมรินทร์, วัฒนชัย; สกุลนุ้ย, วลัยนุช (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to 1) design and develop a mobile-based interactive digital system to support participation management and participation evaluation for Open House event attendees; 2) assess the appropriateness of the developed system; and 3) evaluate attendee satisfaction with the system. The system was designed to support key operational processes, including managing exhibition entries and activity stations, registering and managing participant information, tracking participation across activity stations, enabling voting, and administering questionnaires, as well as generating summaries and reports to support systematic data-driven evaluation. The system was developed using PHP, the MySQL database management system, and the Tailwind CSS framework.          The evaluation involved two groups: five experts in information systems and application development selected through purposive sampling, and 316 actual event participants selected through convenience sampling, with the sample size determined using Yamane’s formula. The results indicated that the system could be successfully implemented and used in the Open House context. Overall, both experts and users reported a high level of satisfaction, particularly with system usability. In conclusion, the developed system demonstrates strong potential to enhance Open House event management and data-driven evaluation of participant engagement, thereby better supporting evidence-based decision-making.